Short-term effects of crop rotations on soil chemical properties under no-tillage condition - Bassegio, Doglas [UNESP]; Santos, Reginaldo Ferreira; Secco, Deonir; Zanão Junior, Luiz Antônio; Werncke, Ivan; Sarto, Marcos Vinícius Mansano [UNESP] (My University, 2015)
The use of crop rotation can provide sustainability for an agricultural production system by improving soil fertility and increasing nutrient use efficiency. Short-term changes in soil chemical properties were studied for different crop rotations and management of crop residues under no-till in Santa Helena, Paraná, Brazil. The investigated crops for the crop rotation were as follows: Pearl millet (Pennisetum glaucum), grass brachiaria (Brachiaria brizantha), forage sorghum (Sorghum bicolor) and sunn hemp (Crotalaria juncea), cropped in autumn-winter as well as an additional treatment in fallow ground (spontaneous weed). The crambe (Crambe abyssinica) was cropped in the winter on all plots. The subplots were divided into either absence or presence of straw mulch mechanical management on the soil surface (Triton). Soil samples were collected at depths of 0-10, 10-20, and 20-40 cm after crambe harvest. Crop rotation with forage sorghum significantly increased (p ≤ 0.05) the K+ exchange (0.14 cmolc dm-3) and organic matter (21.8 g dm-3) contents in the 0-10 and 20-40 cm soil layers, respectively; however, crop rotations had no effect on other soil chemical properties under no-tillage condition. Mechanical management of crop residues had no significant effect on soil chemical properties.
Keywords: Cover crops; Organic matter; Soil fertility; Straw management